2017
DOI: 10.1016/j.bej.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model of catheter-associated urinary tract infections to investigate the role of uncommon bacteria on the Escherichia coli microbial consortium

Abstract: Uncommon bacteria, such as Delftia tusurhatensis have been isolated from CAUTIs in combination with well-established pathogenic bacteria such as Escherichia coli. Nonetheless, the reason why E. coli coexists with other bacteria instead of outcompeting and completely eliminating them is unknown. As such, a flow cell reactor simulating the hydrodynamic conditions found in CAUTIs (shear rate of 15 s −1) was used to characterize the microbial physiology of E. coli and D. tsuruhatensis individually and in consortiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Both model pathogenic strains confirmed their ability to grow in artificial urine medium, as well as to adhere and form stable biofilms on silicone rubber. The ability of E. coli to form robust biofilms on this surface material was previously reported by our research group [52,53]. Moreover, E. coli biofilms exhibited higher cellular densities than S. aureus (Figure 1), demonstrating its higher propensity to form biofilms on silicone.…”
Section: Biofilm Cell Culturabilitysupporting
confidence: 74%
“…Both model pathogenic strains confirmed their ability to grow in artificial urine medium, as well as to adhere and form stable biofilms on silicone rubber. The ability of E. coli to form robust biofilms on this surface material was previously reported by our research group [52,53]. Moreover, E. coli biofilms exhibited higher cellular densities than S. aureus (Figure 1), demonstrating its higher propensity to form biofilms on silicone.…”
Section: Biofilm Cell Culturabilitysupporting
confidence: 74%
“…Forty-five studies were conducted to explore bacterial biofilm formation in bladder models, which corresponds with the current research focus. A total of 36 studies were performed with comparative experimental designs, mainly consisting of comparisons between various coatings of drugs or different materials, including between static and dynamic models in three studies (20,27,30), the comparative analysis of culture fluids in two studies (56,57), comparisons between multiple interventions in 21 studies (13,14,(17)(18)(19)(20)22,(28)(29)(30)36,38,39,41,43,50,(53)(54)(55)58,64), comparisons between infection vectors in eight studies (37,40,42,44,45,52,53,58), and comparisons between experimental temperature in one study (37).…”
Section: Research Design and Content Analysismentioning
confidence: 99%
“…In total, only five studies reported a comparative experiment of in vitro bladder models (20,27,30,56,57), which are summarized in Table S1. Among these, Frant et al (20) suggested that biofilm formation was more prevalent in the BioEncrustation dynamic bladder model and that more substances were observed in the urine scale.…”
Section: Research Design and Content Analysismentioning
confidence: 99%
“…D. tsuruhatensis metabolized citric acid more rapidly leaving more uric acid available in the medium to be used by E. coli for dynamic growth of both organisms. Identification of this organism is not confirmatory with culture, so molecular methods are more reliable [83].…”
Section: Cauti With Delftia Tsuruhatensismentioning
confidence: 99%